La représentation des paysages d’exil dans les arts visuels contemporains : l’exemple du film Parmi nous de Clément Cogitore - Ann Epoudry (Projets de Paysage)
The migratory journey involves crossing territories and the apprehension of the landscapes of these territories raises questions. The landscape can be defined through the feelings evoked by a place, in the complex and multi-sensory physical experience of a space (Paquot, 2016). But it is also, and above all, an aesthetic invention (Roger, 1997) that directs and organises how the world is perceived. Therefore, it also seems interesting to analyse the way in which contemporary art takes into account these landscapes travelled through during journeys of exile. This article seeks to examine how a contemporary work of art can show the impact of migration on the landscape by the reintegration of another lived-in landscape within an existing, socially and politically controlled landscape. Supporting this analysis with Clément Cogitore’s short fiction film Parmi nous (2011), which narrates the attempts of illegal migrants in exile to cross a border zone, we seek to understand how the constructed landscapes of the sets in the film reveal a symbolic and stereotyped landscape and how the relationship between the characters and the landscape, which the artist shows in this work, seems to reinvent the places travelled through and offer a new form of participation within the landscape.